107k views
5 votes
Determine p if the following equation has equal roots: (p-3)xsquare + 4(p-3)x + 4 = 0

User NickZeng
by
7.3k points

1 Answer

3 votes

A quadratic equation
ax^2+bx+c=0 has equal roots if and only if the determinant


\Delta = b^2-4ac

equals zero.

In this case,


a=p-3,\quad b=4(p-3),\quad c=4

So, the determinant is


[4(p-3)]^2-4\cdot (p-3)\cdot 4

Expand the square and multiply terms to get


[4(p-3)]^2-4\cdot (p-3)\cdot 4=16(p-3)^2-16(p-3) = 16(p-3)[(p-3)-1)

Which finally simplifies to


16(p-3)(p-4)

This expression equals zero if one of the factors equals zero:


p-3=0 \iff p=3,\quad p-4=0 \iff p=4

User Zyoma
by
7.2k points